Prognostic impact of extranodal disease on PET/CT in follicular lymphoma: results from a validation study with ECOG 2408 - Frederique St-Pierre; Stephen M. Broski; Zequn Sun; Masha Kocherginsky; Betsy LaPlant; Matthew J. Maurer; Andrew Quon; Lucia Baratto; Hatice Savas; Lale Kostakoglu; Jane N. Winter; Thomas E. Witzig; et al. (Blood Neoplasia, 2025)
Abstract: Parameters detected by positron emission tomography (PET) are not included in the usual predictive indices for follicular lymphoma (FL). Data are lacking regarding PET extranodal (EN) factors that predict outcomes in FL. PET scans from 258 patients with untreated grade 1 to 3A FL included in the E2408 randomized phase 2 trial were reviewed. Validation of the prognostic significance of PET factors identified in a previous retrospective study was performed. PET factors with a significant impact on survival outcomes were combined with significant FL International Prognostic Index 2 (FLIPI-2) factors to evaluate the predictive value of a PET-based prognostic index. Presence of ≥2 EN sites and skin/soft tissue involvement on PET were validated as predictors of overall survival. These factors were combined with all FLIPI-2 factors except “positive bone marrow biopsy” to form a PET-based prognostic score. This novel score identified a group of patients at high risk of progression of disease at 24 months. This PET-based score did not perform better than the traditional FLIPI-2 on additional analysis. Presence of ≥2 EN sites and skin/soft tissue involvement on PET predict poor outcomes in untreated FL. Further studies should be performed to determine the validity of a PET-based prognostic index in FL.